Pengaruh Penerapan Insentif PPh Final UMKM DTP dan Pemahaman Perpajakan Terhadap Kepatuhan WP UMKM Di KPP Pratama Surabaya Sukomanunggal - Ery Nurwijayanti; Budiasih Widiastuti (JEMAP, 2021)
This study aims to determine the effect of the application of the Micro, Small and Medium Enterprises (MSME) Final PPh incentives borne by the government and the understanding of MSME taxpayers' taxation on MSME taxpayer compliance at KPP Pratama Surabaya Sukomanunggal. The research method used is a quantitative method. Sampling was based on purposive sampling method with 100 respondents. Data collection was done by using a questionnaire. The data obtained were processed using Statistical Product and Service Solutions (SPSS) 25. The results showed that the implementation of MSME Final PPh incentives was borne by the government and the understanding of MSME taxpayers' taxation had an effect on MSME taxpayer compliance.